Postnatal Imaging of Antenatal Hydronephrosis - David M. Kitchens; C. D. Anthony Herndon (The Scientific World Journal)
Radiologic imaging of the newborn detected prenatally with hydronephrosis should follow a systematic approach. Upper and lower urinary tract imaging should be performed in most cases in order to determine the etiology and gauge the use of future imaging. An overview of renal ultrasound, voiding cystourethrography, renal scintigraphy, and magnetic resonance urography in the setting of antenatal hydronephrosis are discussed.